Protein Kinase C-Independent Activation of the Epstein-Barr Virus Lytic Cycle - Gradoville, Lyndle (American Society for Microbiology, 2002)
The protein kinase C (PKC) pathway has been considered to be essential for activation of latent Epstein-Barr virus (EBV) into the lytic cycle. The phorbol ester tetradecanoyl phorbol acetate (TPA), a PKC agonist, is one of the best understood activators of EBV lytic replication. Zp, the promoter of the EBV immediate-early gene BZLF1, whose product, ZEBRA, drives the lytic cycle, contains several phorbol ester response elements. We investigated the role of the PKC pathway in lytic cycle activation in prototype cell lines that differed dramatically in their response to inducing agents. We determined whether PKC was involved in lytic cycle induction by histone deacetylase (HDAC) inhibitors. Consistent with prevailing views, B95-8 cells were activated into the lytic cycle by the phorbol ester TPA, via a PKC-dependent mechanism. B95-8 was not inducible by HDAC inhibitors such as n-butyrate and trichostatin A (TSA). Bisindolylmaleimide I, a selective PKC inhibitor, blocked lytic cycle activation in B95-8 cells in response to TPA. In marked contrast, in HH514-16 cells, the immediate-early promoters Zp and Rp were simultaneously activated by the HDAC inhibitors; TPA by itself failed to activate lytic gene expression. Inhibition of PKC activity by bisindolylmaleimide I did not block lytic cycle activation in HH514-16 cells by n-butyrate or TSA. In an extensive exploration of the mechanism underlying these different responses we found that the variable role of the PKC pathway in the two cell lines could not be accounted for by significant polymorphisms in the promoters of the immediate-early genes, by differences in the start sites of immediate-early gene transcription, or by differences in the nucleosomal organization of EBV DNA in the region of Zp or Rp. While B95-8 cells contained more total PKC activity than did HH514-16 cells in an in vitro assay, another EBV-transformed marmoset lymphoblastoid cell line, FF41, in which the lytic cycle was not inducible by TPA, contained comparably high levels of PKC activity. Moreover, two marmoset lymphoblastoid cells lines in which the lytic cycle could not be triggered by TPA maintained the same profile of EBV latency proteins as B95-8 cells. Thus, the profile of EBV latency proteins did not account for susceptibility to induction by PKC agonists. PKC activation is neither obligatory nor sufficient for the switch between latency and lytic cycle gene expression of EBV in many cell backgrounds. Lytic cycle induction by HDAC inhibitors proceeds by a PKC-independent mechanism.